Organisational Behaviour and Management - Martin, John (Prentice Hall/Financial Times, 2005)
This comprehensive and accessible introduction to organizational behaviour balances sociological and psychological perspectives to provide the perfect core text for students at undergraduate and MBA level. John Martin successfully blends together theory, practical application and critical reflection and encourages students to develop practical and theoretical understanding. Written in a clear and engaging way the text includes learning objectives, discussion and research questions, management in action' panels, stop and consider' boxes and excellent chapter summaries. There is an accompanying website that includes extensive resources for both you and your students